Principles and a conceptual model for working multisectorally - Garrett, James; Bassett, Lucy; Levinson, F. James (International Food Policy Research Institute, 2011)
The motivation for a multisectoral approach to nutrition applies whether we are talking about complex multicomponent programs or more straightforward integration of nutrition activities into programs being undertaken by sectors outside health. Adding a nutrition education component to a home-gardening project being promoted by the Ministry of Agriculture, for instance, is one example of straightforward integration. The focus of this volume, however, is on programs that address the more complex institutional challenge of working across sectors. By this we mean programs that attempt to integrate activities or components across ministries, institutions, or agencies that have fundamentally different missions, such as agriculture, education, or health. So here we are looking beyond cross- or intersectoral programs in which nutrition activities might simply span or link two or more sectors. Rather, our case studies are of programs that comprehensively involve multiple institutions (ministries or agencies) in systematic efforts to address problems of malnutrition.